2010
DOI: 10.1029/2009jd012829
|View full text |Cite
|
Sign up to set email alerts
|

Examining the impact of overlying aerosols on the retrieval of cloud optical properties from passive remote sensing

Abstract: [1] Haywood et al. (2004) show that an aerosol layer above a cloud can cause a bias in the retrieved cloud optical thickness and effective radius. Monitoring for this potential bias is difficult because space-based passive remote sensing cannot unambiguously detect or characterize aerosol above cloud. We show that cloud retrievals from aircraft measurements above cloud and below an overlying aerosol layer are a means to test this bias. The data were collected during the Intercontinental Chemical Transport Expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(107 citation statements)
references
References 36 publications
5
102
0
Order By: Relevance
“…Haywood et al, 2004;Cattani et al, 2006;Bennartz and Harshvardhan, 2007;Wilcox et al, 2009;Coddington et al, 2010). In support of the presented analysis, potential biases in r e have been shown to be less than 1 µm for retrievals where the visible reflectance is matched with the 3.7 µm or 2.13 µm reflectance.…”
Section: Above-cloud Aerosol Layerssupporting
confidence: 49%
“…Haywood et al, 2004;Cattani et al, 2006;Bennartz and Harshvardhan, 2007;Wilcox et al, 2009;Coddington et al, 2010). In support of the presented analysis, potential biases in r e have been shown to be less than 1 µm for retrievals where the visible reflectance is matched with the 3.7 µm or 2.13 µm reflectance.…”
Section: Above-cloud Aerosol Layerssupporting
confidence: 49%
“…The transport of Saharan mineral dust is also frequent across the Atlantic, and dust plumes are regularly transported above low-level clouds off the coasts of Senegal . Other types of aerosols such as volcanic dust particles and pollutant particles (Hsu et al, 2003;Coddington et al, 2010) were also observed above clouds in other regions of the world. The most commonly observed situation corresponds to an elevated aerosol layer suspended above a low-level liquid water cloud, but properties of aerosol above clouds (AAC) have not been extensively studied yet.…”
Section: Introductionmentioning
confidence: 97%
“…It is found that the vertical structure induced by drizzle and 3-D radiative effects operate together to cause dramatic differences between the 1.6, 2.1, and 3.7 µm retrievals (Zhang et al, 2012;Zhang, 2013;Nakajima et al, 2010a, b;Nagao et al, 2013). In addition, the water vapor absorption within a cloud and the presence of an absorbing aerosol layer above a cloud leads to a positive bias in the retrieval (Alexandrov et al, 2012a;Coddington et al, 2010;Haywood et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The CDR values of the clouds ranged from 5 to 20 µm in 1 µm increments, and the EV values were 0.01, 0.02, and 0.05. Three COT values (1, 5, and 10) were considered in this study, and the contributions from the underlying surface and the aerosol and molecule layers are negligible (Coddington et al, 2010;Goloub et al, 2000). The Rayleigh optical thickness for different wavelengths was set according to the results of Bodhaine et al (1999).…”
Section: Polder-like Observations Simulated With the Rt3 Modelmentioning
confidence: 99%